Hyponatraemia in Community Acquired Bacterial and Tubercular Meningitis in Hospital Admitted Adult Patients - Sengupta, Poly; Ali, Md. Roushan; Mohammed, Fazle Rabbi; Biswas, Rama; Rashid, Mamunur; Nahar, Shamshun (Journal of Medicine, 2014)
Background: Bacterial and Tubercular Meningitis is a life-threatening disease. Hyponatraemia in bacterial and tubercular meningitis is a known complication with unknown true prevalence and clinical importance. This study was conducted to find out how commonly hyponatraemia occurs in community acquired bacterial and tubercular meningitis, to evaluate its severity, to see the pattern of presentation and to observe the level of consciousness. Materials and Methods: It was a descriptive cross sectional study performed in 30 admitted patients with clinically diagnosed bacterial and tubercular meningitis in medicine wards of Medical College for Women & Hospital (MCWH) and Dhaka Medical College & Hospital (DMCH) since August 2009 to March 2010. Serum electrolyte and level of consciousness on admission was recorded in all patients. Results: Twenty Nine patients (96.7%) with meningitis had hyponatraemia, serum sodium level ranged from 115-138 mmol/l; mean sodium level is 128.57 ± 5.56 SD mmol/L. Serum sodium level was mild (>125-135 mmol/L) in 20 (66.7%) patients with meningitis and moderate (110-125 mmol/L) in 9 (30%) and severe (<110 mmol/L) in 1 (3.3%) patient. GCS ranged from 8 to 14, mean 11.56±1.40 SD in day 1. In tubercular meningitis (n=8) and bacterial meningitis (n=22) serum sodium level was 128.63±7.44 and 128.55±4.93 while mean GCS was 11.38±2.13 and 11.95±1.40 respectively on the day of admission. Conclusion: Although the true prevalence, severity and clinical importance of hyponatraemia in bacterial meningitis are unknown, its presence may influence the outcome in such patients depending on severity. So knowledge about its prevalence and severity will guide physicians to take decisions about its management. DOI: http://dx.doi.org/10.3329/jom.v15i2.20682 J MEDICINE 2014; 15 : 114-117